MARKETING MIX STRATEGY DETERMINANTS AND SOCIAL MEDIA IN VETERINARY-BASED BUSINESS: EXPERIENCE FROM SERBIA - Ilic, Milena P.; Gojković, Milica; Blažić, Ksenija; Radi Ciuperca, Karla; Simion, Violeta-Elena (Journal of Economic Development, Environment and People, 2021)
The paper is dedicated to testing the entrepreneurial idea of founding a service micro company in the field of veterinary medicine - Animal Care. The starting point is the theoretical aspect of marketing mix services observed through the prism of a specific company in the field of agribusiness. For the needs of the research, secondary sources were used and a survey was conducted which gave the results of the influence of the elements of marketing mix services on marketing communication towards the users of the company Animal Care. It was determined that the effects of promotion, especially in the field of digital marketing, directly affect the increase in sales of products and services, and thus the satisfaction of consumers & users in veterinary services. The results of the research provided answers to research questions and helped the entrepreneur to understand that selected elements of the marketing mix help in the promotion of products and services of Animal Care companies. Respondents showed interest in using the services of the Animal Care company with the help of the Animal Care android application and website as a selected distribution channel, but also for the promotion of new services and offers of the company.